Intelligent Bat Algorithm for Finding Eps Parameter of DbScan Clustering Algorithm - Ghathwan, Khalil Ibrahim; Mohammed, Athraa Jasim (Iraqi Journal of Science, 2022)
Clustering is an unsupervised learning method that classified data according to similarity probabilities. DBScan as a high-quality algorithm has been introduced for clustering spatial data due to its ability to remove noise (outlier) and constructing arbitrarily shapes. However, it has a problem in determining a suitable value of Eps parameter. This paper proposes a new clustering method, termed as DBScanBAT, that it optimizes DBScan algorithm by BAT algorithm. The proposed method automatically sets the DBScan parameters (Eps) and finds the optimal value for it. The results of the proposed DBScanBAT automatically generates near original number of clusters better than DBScanPSO and original DBScan. Furthermore, the proposed method has the ability to generate high quality clusters with minimum entropy [ 0.2752, 0.4291] in TR11 and TR12 datasets.